2007
DOI: 10.1111/j.1365-2929.2007.02747.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of three cultural competency measures

Abstract: ability to recognise appropriate methods for action and risk assessment. Based on these findings, this course content was effective in significantly improving student awareness of patient safety culture and in developing skills necessary to break the cycle of medical error. Context and setting Since the Liaison Committee on Medical Education has required that all medical schools in the USA offer cultural competency training, several surveys have been developed to measure cultural competency. However, these cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…We assessed demographic information that might affect students’ baseline cultural competence (age, gender, residence, and nationality). We also administered a survey containing three cultural competence self-assessment scales 12 and compared the scores of the control and intervention groups. There were no significant differences in student age, gender, nationality, or prior communication skills and cultural competence training between the control and the intervention groups.…”
Section: Methodsmentioning
confidence: 99%
“…We assessed demographic information that might affect students’ baseline cultural competence (age, gender, residence, and nationality). We also administered a survey containing three cultural competence self-assessment scales 12 and compared the scores of the control and intervention groups. There were no significant differences in student age, gender, nationality, or prior communication skills and cultural competence training between the control and the intervention groups.…”
Section: Methodsmentioning
confidence: 99%
“…As with many Eastern countries, the adoption of Western ideas always brings up a valid question: do the assumptions of the Western model apply to our own circumstances? In the same vein, research into cultural competence in Taiwan began with forays into the applicability of Western‐developed frameworks in Taiwanese settings . Although medical schools across Taiwan are encouraged to incorporate cultural competence into their curricula, there has been no unified strategy thus far for doing so.…”
Section: Introductionmentioning
confidence: 99%
“…In the same vein, research into cultural competence in Taiwan began with forays into the applicability of Western-developed frameworks in Taiwanese settings. 22,23 Although medical schools across Taiwan are encouraged to incorporate cultural competence into their curricula, there has been no unified strategy thus far for doing so.…”
mentioning
confidence: 99%
“…In other studies, the IAPCC‐R showed evidence of acceptable reliability 16 , 17 and acceptable validity 18 . However, a study conducted in Taiwan found weak reliability and a weak internal structure, 19 while a U.S. study reported weak internal consistency and low item‐total correlation 20…”
Section: Existing Instrumentsmentioning
confidence: 92%